An exploration of moral hazard behaviors under the national health insurance scheme in Northern Ghana: a qualitative study. Issue 1 (June 2015) - Debpuur, Cornelius; Dalaba, Maxwell; Chatio, Samuel; Adjuik, Martin; Akweongo, Patricia
Abstract Background The government of Ghana introduced the National Health Insurance Scheme (NHIS) in 2003 through an Act of Parliament (Act 650) as a strategy to improve financial access to quality basic health care services. Although attendance at health facilities has increased since the introduction of the NHIS, there have been media reports of widespread abuse of the NHIS by scheme operators, service providers and insured persons. The aim of the study was to document behaviors and practices of service providers and clients of the NHIS in the Kassena-Nankana District (KND) of Ghana that constitute moral hazards (abuse of the scheme) and identify strategies to minimize such behaviors. Methods Qualitative methods through 14 Focused Group Discussions (FGDs) and 5 individual in-depth interviews were conducted between December 2009 and January 2010. Thematic analysis was performed with the aid of QSR NVivo 8 software. Results Analysis of FGDs and in-depth interviews showed that community members, health providers and NHIS officers are aware of various behaviors and practices that constitute abuse of the scheme. Behaviors such as frequent and 'frivolous' visits to health facilities, impersonation, feigning sickness to collect drugs for non-insured persons, over charging for services provided to clients, charging clients for services not provided and over prescription were identified. Suggestions on how to minimize abuse of the NHIS offered by respondents included: reduction of premiums and registration fees, premium payments by installment, improvement in the picture quality of the membership cards, critical examination and verification of membership cards at health facilities, some ceiling on the number of times one can seek health care within a specified time period, and general education to change behaviors that abuse the scheme. Conclusion Attention should be focused on addressing the identified moral hazard behaviors and pursue cost containment strategies to ensure the smooth operation of the scheme and enhance its sustainability.